Challenges and recent advances in photodiodes-based organic photodetectors. (December 2021) - Liu, Junwei; Gao, Mengyuan; Kim, Juhee; Zhou, Zhihua; Chung, Dae Sung; Yin, Hang; Ye, Long
Graphical abstract: Abstract: Organic photodetectors (OPDs) have drawn extensive research efforts due to their tailorable spectral response, ease of processing, compatibility with flexible devices and cooling-free operations. In this review, we outline the promising strategies for constructing high-performance and highly stable photodiodes-based OPDs from the perspectives of molecular engineering, morphology control, and device structure design. Firstly, the impact of molecular design and morphology control on OPD performance is clearly underlined and the molecular design rules and quantitative analysis methods are presented for high-performance OPDs. Subsequently, some striking device designs for multifunctional applications are discussed to elucidate the corresponding mechanism for various responses. What follows are the research efforts of boosting OPD stability for commercial applications. This review not only presents the detailed discussion on various OPD strategies aiming at simultaneously enhancing performance and stability but also provides some insights for the remaining challenges to make further breakthrough of OPDs.